PERAN E-COMMERCE DALAM MENGEMBANGKAN BISNIS DI ERA DIGITAL - mel, melati melati (JURNAL DIALOKA: Jurnal Ilmiah Mahasiswa Dakwah dan Komunikasi Islam, 2024)
In the digital era, business actors must identify the potential and opportunities available to expand their business. Advancements in the digital era present increasingly sharp challenges and competition in capturing markets. E-commerce, as an online transaction system, facilitates business actors in interacting with customers through the internet. This research utilizes a qualitative method, namely through library research, by referencing several journals obtained from Google Scholar. The research concludes that e-commerce plays a role in developing businesses in the digital era. This role includes expanding market reach, facilitating product marketing and payment, improving operational efficiency, saving costs, providing easy access to website features, and providing customer data. Business actors also need to address challenges in business such as fraud, hacking, and price competition.